The factors influencing employees’ job performance of work-from-home practices in the corporate sector in Malaysia. - Kamleswari, Muraly (2025)
The main objective of this research is to study the effect of communication, perceived organizational support and home work environment towards job performance in corporate sector. The inconsistency of findings in past literature between the independent variable has prompted researchers to explain the inconsistency. The survey questionnaire was distributed using an online questionnaire to employees working in corporate sector. A total of 207 questionnaires were used for analysis. The direct relationship was analyzed using the PLS-SEM method. The results show that communication, perceived organizational support and home-work environment have a significant relationship with employees’ job performance in working-from-home setting. Finally, management implications, study limitations, and future research recommendations are discussed.